Photocatalysis and Photodynamic Therapy in Diabetic Foot Ulcers (DFUs) Care: A Novel Approach to Infection Control and Tissue Regeneration - Paweł Mikziński; Karolina Kraus; Rafał Seredyński; Jarosław Widelski; Emil Paluch (Molecules)
Photocatalysis and photodynamic therapy have been increasingly used in the management of diabetic foot ulcers (DFUs), and their integration into increasingly innovative treatment protocols enables effective infection control. Advanced techniques such as antibacterial photodynamic therapy (aPDT), liposomal photocatalytic carriers, nanoparticles, and nanomotors—used alone, in combination, or with the addition of antibiotics, lysozyme, or phage enzymes—offer promising solutions for wound treatment. These approaches are particularly effective even in the presence of comorbidities such as angiopathies, neuropathies, and immune system disorders, which are common among diabetic patients. Notably, the use of combination therapies holds great potential for addressing challenges within diabetic foot ulcers, including hypoxia, poor circulation, high glucose levels, increased oxidative stress, and rapid biofilm formation—factors that significantly hinder wound healing in diabetic patients. The integration of modern therapeutic strategies is essential for effective clinical practice, starting with halting infection progression, ensuring its effective eradication, and promoting proper tissue regeneration, especially considering that, according to the WHO, 830 million people worldwide suffer from diabetes.